A New Method for Double-Eyelid Blepharoplasty Using Orbital Septum. Issue 6 (December 2018) - Li, Gaofeng; Ding, Wei; Tan, Jun; Zhang, Bo; Chen, Xin; He, Bin
Abstract : Background: This article presents a new method using orbital septum for double-eyelid blepharoplasty. Methods: During double-eyelid blepharoplasty, we incised the orbital septum horizontally. Using the attachment site of the levator aponeurosis as a pedicle, the lower part of the dissected orbital septum was turned downward and then sutured to the upper border of the lower orbicularis oculi muscle and posterior pretarsal fascia. We evaluated the efficacy of this double-eyelid surgical procedure in patients undergoing the procedure from December 2015 to October 2017. Results: We included 462 eyes of 231 patients in the final analysis. Sutures were removed 7 days after surgery. All double-eyelid creases were well formed, and the eyelids closed well. Six-month follow-up results revealed that the double-eyelid shape was natural looking, and no patients experienced upper eyelid retraction or incomplete eye closure. Notched scars did not occur, and patient satisfaction was achieved in all cases. Two hundred eleven patients were fully satisfied with the surgical results, and 20 were basically satisfied with the surgical results. Conclusions: Using the orbital septum is a good approach for double-eyelid blepharoplasty. Abstract : Supplemental digital content is available in the text.